Wildlife of the world - Beer, Amy-Jane; Harvey, Derek; Hoare, Ben; Hume, Rob; Jackson, Tom, 1972-; Parker, Steve, 1952-; Parsons, Katie; Woodward, John, 1954- (DK Publishing, 2015)
Profiles over four hundred animals from around the world, discussing their habitat, physical characteristics, and challenges they face.